The sacredness of the person : a new genealogy of human rights - Joas, Hans, 1948- (Georgetown University Press, 2013)
What are the origins of the idea of human rights and universal human dignity? How can we most fully understand -- and realize -- these rights going into the future? In The Sacredness of the Person, internationally renowned sociologist and social theorist Hans Joas tells a story that differs from conventional narratives by tracing the concept of human rights back to the Judeo-Christian tradition or, alternately, to the secular French Enlightenment. While drawing on sociologists such as Émile Durkheim, Max Weber, and Ernst Troeltsch, Joas sets out a new path, proposing an affirmative genealogy in which human rights are the result of a process of "sacralization" of every human being.